The Causal Effects of World War II Military Service - Alex Cousley; Peter Siminski; Simon Ville (Institute for the Study of Labor (IZA), 2016)
The effects of military service have been studied for decades, but surprisingly few studies have estimated the effects of World War II (WW2) service, where the focus has been on the impact of this 'total war' on the broader civilian population. Over 90% of Australian males born in the early 1920s served in the military during WW2. Almost none of those born in the late 1920s served. Treating such cohort differences as exogenous, we conduct one of the first econometric studies of WW2 service. We consider major life outcomes including employment, marital status and home ownership, all measured in 1966, while the economy was strong and male employment was very high. We find a significant negative effect on employment, half of which is accompanied by pensioner status. We find positive effects on home ownership and on separation/divorce. A feature of our analysis is a novel visual depiction of the variation which identifies the estimates, drawing on the Frisch-Waugh theorem.
Keywords: H56; N37; N47; 330; military service; Australia; World War Two; Frisch-Waugh theorem